Novel Babesia bovis exported proteins that modify properties of infected red blood cells - Hakimi, Hassan; Templeton, Thomas J.; Sakaguchi, Miako; Yamagishi, Junya; Miyazaki, Shinya; Yahata, Kazuhide; Uchihashi, Takayuki; Kawazu, Shin-ichiro; Kaneko, Osamu; Asada, Masahito (PLOS Pathogens, 2020)
Babesia bovis causes a pathogenic form of babesiosis in cattle. Following invasion of red blood cells (RBCs) the parasite extensively modifies host cell structural and mechanical properties via the export of numerous proteins. Despite their crucial role in virulence and pathogenesis, such proteins have not been comprehensively characterized in B. bovis. Here we describe the surface biotinylation of infected RBCs (iRBCs), followed by proteomic analysis. We describe a multigene family (mtm) that encodes predicted multi-transmembrane integral membrane proteins which are exported and expressed on the surface of iRBCs. One mtm gene was downregulated in blasticidin-S (BS) resistant parasites, suggesting an association with BS uptake. Induced knockdown of a novel exported protein encoded by BBOV_III004280, named VESA export-associated protein (BbVEAP), resulted in a decreased growth rate, reduced RBC surface ridge numbers, mis-localized VESA1, and abrogated cytoadhesion to endothelial cells, suggesting that BbVEAP is a novel virulence factor for B. bovis.